2017
DOI: 10.1186/s12912-016-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Finnish Neecham Confusion Scale and Nursing Delirium Screening Scale using Confusion Assessment Method algorithm as a comparison scale

Abstract: BackgroundDelirium is a common clinical problem with acute and fluctuating onset. Early notification of its symptoms can lead to earlier detection and management of this state. Valid and reliable instruments are required for successful nursing practice. The purpose of the study was to psychometrically test the Finnish versions of the Neecham Confusion Scale (NEECHAM) and the Nursing Delirium Screening Scale (Nu-DESC) in surgical nursing care, utilizing the Confusion Assessment Method (CAM) algorithm as a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 33 publications
2
32
1
2
Order By: Relevance
“…According to van Velthuijsen et al (2016), as the NEECHAM is a tool combining interactive and observational aspects, it takes longer to administer and is therefore more time-consuming, and training is required for nurses. Finnish authors Poikajärvi et al (2017) tested and compared the properties of the NEECHAM and the NU-DESC and confirmed that both tools are reliable and practical for use by nurses. In terms of validity of both tools, they suggest further testing.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…According to van Velthuijsen et al (2016), as the NEECHAM is a tool combining interactive and observational aspects, it takes longer to administer and is therefore more time-consuming, and training is required for nurses. Finnish authors Poikajärvi et al (2017) tested and compared the properties of the NEECHAM and the NU-DESC and confirmed that both tools are reliable and practical for use by nurses. In terms of validity of both tools, they suggest further testing.…”
Section: Discussionmentioning
confidence: 87%
“…AUC and ROC ranged between 0.76 (Lingehall et al, 2012) and 0.99 (Radtke et al, 2010). Reliability ranged from 0.47 (Poikajärvi et al, 2017) to 0.94 (Spedale et al, 2016). Cut off score ranged from 2 to 3 (Table 2).…”
Section: The Nurses Delirium Screening Checklist (Nu-desc)mentioning
confidence: 99%
See 3 more Smart Citations